Malignant Hidroacanthoma Simplex: A Case Report - Ren, Xiangxiang; Xie, Tianhao; Liu, Lingyun; Yang, Fan; Zhang, Meng (Case reports in dermatology, 2025)
Introduction: Malignant hidroacanthoma simplex (MHS) is an exceedingly rare cutaneous neoplasm with limited documented cases. This report highlights a distinctive case of MHS with prolonged clinical evolution, emphasizing its diagnostic challenges and management outcomes. Case Presentation: A 64-year-old female presented with a right lumbar mass persisting for over 2 decades, exhibiting progressive enlargement in the past 5 years. Clinical examination revealed a solitary reddish-brown proliferative plaque (3.5 cm × 4.0 cm) on the right waist, characterized by irregular borders, a rough surface, and reddish-brown crusts. Histopathological findings included hyperkeratosis, irregular epidermal hyperplasia, hypertrophic stratum spinosum, and tumor cells displaying pale eosinophilic cytoplasm, vacuolated nuclei, small nucleoli, and atypical mitotic figures. Notably, tumor cells were confined to the epidermis without dermal invasion. The patient underwent local extended excision, and postoperative surveillance over 15 months demonstrated no evidence of recurrence or lymph node metastasis. Conclusion: This case underscores the indolent yet locally persistent nature of MHS. Complete surgical excision remains the cornerstone of management, with favorable outcomes achievable in the absence of dermal infiltration. Long-term follow-up is critical to monitor potential recurrence.